2012
DOI: 10.1002/hed.23104
|View full text |Cite
|
Sign up to set email alerts
|

Factors predisposing to chyle leakage following thyroid cancer surgery without lateral neck dissection

Abstract: If extensive central compartment node dissection is needed, meticulous dissection is required, especially in male patients, and aged >45 years, even without lateral neck dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…2,[9][10][11] Several studies have reported chyle leakage incidences of 0.6%-1.4% after CND and 4.5%-8.3% after lateral neck dissection. 3,[5][6][7] In this study, the overall incidence of chyle leakage after thyroidectomy or CND was 0.9%, whereas in patients who underwent therapeutic lateral neck dissection it was 3.9%. This is slightly lower than the incidence reported in previous studies, which might be related to the increased use of ultrasonic energy devices enabling meticulous vessel sealing and improved surgical techniques.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…2,[9][10][11] Several studies have reported chyle leakage incidences of 0.6%-1.4% after CND and 4.5%-8.3% after lateral neck dissection. 3,[5][6][7] In this study, the overall incidence of chyle leakage after thyroidectomy or CND was 0.9%, whereas in patients who underwent therapeutic lateral neck dissection it was 3.9%. This is slightly lower than the incidence reported in previous studies, which might be related to the increased use of ultrasonic energy devices enabling meticulous vessel sealing and improved surgical techniques.…”
Section: Discussionmentioning
confidence: 55%
“…As for the incidence of chyle leakage, the proportion of chyle leakage after CND was very high in our study compared with previous studies. However, because Lee et al reported a 0.6% incidence of chyle leakage in 2314 patients with CND, and another study reported an incidence of 1.4% in 283 patients, it is clear that chyle leakage can occur even after central neck compartment dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical reexploration should be considered only after conservative measures have either been exhausted or deemed ineffective. Suggested criteria for reexploration range from outputs of >500 mL/day to >1000 mL/day output for 5 days [ 1 , 8 , 22 , 66 ]. Although the recommended criteria for reexploration vary considerably, the general sense is that surgical reexploration should take place when a CL does not respond appropriately to conservative management.…”
Section: Treatment Options For Chyle Leaksmentioning
confidence: 99%
“…Chyle leak (CL) from iatrogenic thoracic duct injury is a rare but serious complication of head and neck surgery that occurs in 0.5–1.4% of thyroidectomies [ 1 4 ] and 2–8% of neck dissections [ 5 8 ]. The variable anatomy and fragile composition of the thoracic duct render it prone to inadvertent injury.…”
Section: Introductionmentioning
confidence: 99%
“…Because the exact incidence of chyle leakage after esophagectomy has not been reported, we can infer its incidence from the results of head and neck surgery as 0.5%-1.4% of thyroidectomies [49,50] and 2%-8% of neck dissections [51,52]. If the surgeons perform 3-field lymph node dissection, chyle leakage at the neck theoretically occurs in 2%-8% of cases, but the real chyle leakage incidence after esophagectomy might be lower than that assumption.…”
Section: Chyle Leakage At the Neckmentioning
confidence: 96%